Development of Multimedia for Learning Attitude Improvement of Biological Laboratory Techniques Subject for Grade 11 High School Students - ปุรณะวิทย์, คีต์รามิลธ์; ปฐมอารีย์, วสุ (Progress in Applied Science and Technology, 2017)
This research objectives are 1) to construct a multimedia on microbiological procedure for determination of water quality for consumption and 2) to study learning attitude of students on the prepared multimedia in the classroom. The target group is 73 grade 11 high school students from Hongsonsuksa School in academic year 2016. Research tools are as follow 1) A unit lesson plan of 3 periods on microbiological laboratory techniques for water quality examination 2) Students’ behavior observation record 3) Students’ team work record 4) Attitude test questionnaire of students and 5) students’ informal interviewing record. The research process started with observation of students’ behavior in classroom with old teaching style, then construction of the multimedia and used in the classroom again with the same group of students, observed their behaviors when study in class using the multimedia and collected the attitude test questionnaire. The result showed that 1) the multimedia’s quality is good ( = 4.42, S.D. = 0.24) 2) Students were satisfied learning with the multimedia used in the classroom. They agreed that the media helped them understand the lesson more at most agreed level ( = 4.78, S.D. = 0.42). Students agreed that the multimedia attracted their interest in the lesson and promote their enthusiasm at most agreed level ( = 4.95, S.D. = 0.23). They also agreed that the multimedia made them feel more likely to join the team and participate in class activities at very agreed level ( = 4.42, S.D. = 0.50).